A Role for Systemic Inflammation in Stroke-Associated Infection and the Long-Term Prognosis of Acute Ischemic Stroke: A Mediation Analysis - Huang S; Xie W; Gao Y; Jin Y; Chen Y; Zhou G; Chen F; Jin Q; Wu Z; Wang L; Chen C; Weng Y; et al. (Dove Medical Press, 2024)
Suwen Huang,1,* Wei Xie,1,2,* Yufan Gao,1,3,* Yining Jin,1,3 Yilin Chen,1,2 Guoliang Zhou,1,2 Feng Chen,1,2 Qiaoqiao Jin,1,2 Zihao Wu,1,2 Lingsheng Wang,1,2 Chao Chen,4 Yiyun Weng,1 Guangyong Chen5 1Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China; 2The First School of Medicine, School of Information and Engineering, Wenzhou Medical University, Wenzhou, People's Republic of China; 3The Second School of Medicine, Wenzhou Medical University, Wenzhou, People's Republic of China; 4Department of Nutriology, The Third Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China; 5Department of Neurology, The Third Affiliated Hospital of Wenzhou Medical University, Wenzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Guangyong Chen, Department of Neurology, The Third Affiliated Hospital of Wenzhou Medical University, Wenzhou, People's Republic of China, Email gychen@wmu.edu.cn Yiyun Weng, Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China, Email wengyiyun2012@126.comBackground and Purpose: The dynamic systemic inflammation level and stroke-associated infection (SAI) are related to the prognosis of acute ischemic stroke (AIS). We aimed to explore whether the systemic inflammatory response index (SIRI), systemic immune inflammation index (SII), and their dynamic changes possess predictability for SAI and long-term prognosis.Methods: A total of 1804 AIS patients without intravenous thrombolysis in two hospitals were included. We explored the relationship between SIRI, SII, and their dynamic changes and outcomes by constructing clusters. The mediating effects of SAI between prognosis and systemic inflammation were further evaluated.Results: Each SD increase in the concentration of SIRI exhibited a significant correlation with the risk of poor functional outcome, mortality, and functional dependency. Through K-means clustering analysis, patients with dramatically elevated or decreased systemic inflammation levels of SIRI (OR: 2.293, 95% CI: 1.279- 4.109) and SII (OR: 3.165, 95% CI: 1.627- 6.156) within 7 days had a higher risk of functional outcome. Through mediation analysis, SAI mediated the association between systemic inflammation and poor prognosis (SIRI: 33.73%, SII: 16.01%).Conclusion: Dramatically changing dynamics of SIRI and SII were significantly associated with a higher risk of poor prognosis in AIS patients. SAI mediated the association between systemic inflammation and prognosis at 1 year.Keywords: AIS, inflammation, SAI, mediation analysis, clustering analysis